Association of Campylobacter jejuni infection and GuillainBarré syndrome: a cohort study in the northwest of Iran - Barzegar, Mohammad; Alizadeh, Asghar; Toopchizadeh, Vahideh; Dastgiri, Saeed; Majidi, Jafar (The Turkish Journal of Pediatrics, 2008)
Recent studies have suggested that Campylobacter jejuni is a common pathogen causing Guillain-Barré syndrome (GBS). This study aimed to determine the frequency and clinical and electrophysiological features of C. jejuni infection in children with GBS. We carried out a prospective study on a cohort of 48 children with GBS admitted to Tabriz Children's Hospital in the northwest of Iran from January 2003 to March 2005. Serologic investigations were used to diagnose preceding C. jejuni infection. Evidence of a recent C. jejuni infection was found in 23 (47.9%) of the patients. C. jejuni-associated GBS patients were younger than others (p = 0.010), and they had a rapid progression to reach peak disability (p = 0.018). Neither the peak disability nor the residual one-year disability was different between the C. jejuni- positive and C. jejuni-negative patients. The patients with preceding C. jejuni infection were more likely to have axonal neuropathy (p = 0.021).